Nomenclature for human and animal fungal pathogens and diseases: a proposal for standardized terminology - de Hoog, Sybren; Walsh, Thomas J; Ahmed, Sarah A; Alastruey-Izquierdo, Ana; Arendrup, Maiken Cavling; Borman, Andrew; Chen, Sharon; Chowdhary, Anuradha; Colgrove, Robert C; Cornely, Oliver A; Denning, David W; Dufresne, Philippe J; et al. (Journal of clinical microbiology, 2024)
Medically important pathogenic fungi invade vertebrate tissue and are considered primary when part of their nature life cycle is associated with an animal host and are usually able to infect immunocompetent hosts. Opportunistic fungal pathogens complete their life cycle in environmental habitats or occur as commensals within or on the vertebrate body, but under certain conditions can thrive upon infecting humans. The extent of host damage in opportunistic infections largely depends on the portal and modality of entry as well as on the host's immune and metabolic status. Diseases caused by primary pathogens and common opportunists, causing the top approximately 80% of fungal diseases [D. W. Denning, Lancet Infect Dis, 24:e428-e438, 2024, https://doi.org/10.1016/S1473-3099(23)00692-8], tend to follow a predictive pattern, while those by occasional opportunists are more variable. For this reason, it is recommended that diseases caused by primary pathogens and the common opportunists are named after the etiologic agent, for example, histoplasmosis and aspergillosis, while this should not be done for occasional opportunists that should be named as [causative fungus] [clinical syndrome], for example, Alternaria alternata cutaneous infection. The addition of a descriptor that identifies the location or clinical type of infection is required, as the general name alone may cover widely different clinical syndromes, for example, "rhinocerebral mucormycosis." A list of major recommended human and animal disease entities (nomenclature) is provided in alignment with their causative agents. Fungal disease names may encompass several genera of etiologic agents, consequently being less susceptible to taxonomic changes of the causative species, for example, mucormycosis covers numerous mucormycetous molds.
Keywords: terminologie jako téma; proposal; Terminology as Topic; oportunní infekce; fungal disease; mykózy; houby; Animals; nomenclature; Humans; Mycoses; Opportunistic Infections; lidé; Fungi; zvířata